"Pedro Páramo", la infernalización del purgatorio y el llamado Milagro Mexicano - Pérez Hernández, Diego Octavio (2023)
The purpose of this article is to interpret the use of infernal imagery in Juan Rulfo’s Pedro Páramo. The defended hypothesis argues that the symbolic realm of Comala is a hellish purgatory, one without hope. Thus, the novel implies a contravention of the hopeful connotations associated with the so-called Mexican Miracle, not only because infernal despair is the antithesis of the optimism linked to the capitalist development that Mexico pursued, but also because this hopelessness is the result of the abandonment by a series of administrations that favored industrial interests at the expense of the educational needs of large segments of the population.